Recursos educacionais para o ensino introdutório à computação usando impressora 3D e gamificação - Ribeiro, Leonardo Corrá Pires Trone (2019)
Context: Studies in the literature point to a high dropout in higher education courses. Given the importance of this sector for the technological development of the country, it is extremely important to develop teaching methods that foster the interest of high school students who may enter the area, so that there is a reduction in this dropout in computer courses. New technologies are known to attract people’s interest and 3D printing is one of the most prominent examples of technology today. In addition, game concepts also help to attract people’s cognitive interest in learning. In this context, this work proposes an approach that combines concepts of 3D printing and gamification in order to increase the attractiveness of courses in the computing field. Objective: The aim of this work was to generate a set of educational resources to teach the basics of programming in order to introduce the area of computing. Method: To this end, several programming teaching methods were analyzed, together with 3D modeling tools. In order to try to unite both concepts, a 3D modeling tool using programming called Madeup was modified, adding gamification concepts to increase its attractiveness. In addition, a course based on this tool was developed, teaching the basics of using the tool, early programming and 3D modeling concepts, in order to be able to perform maker-style activities. Results: With the end of the research, we have a gamified tool for 3D modeling using programming, as well as a programming teaching course that takes advantage of the concept of 3D modeling and printing as well as the gamification of the tool. Conclusions: The development of educational resources requires research and reasoning about the concepts to be addressed with these resources, and the greater the number of concepts to be considered, the greater the dificulty to relate and unite them. This also applies to motivational mechanisms, which can be dificult to relate to, as in the case of this work they are two completely diferent mechanisms. As future work, we will use the educational resources with high school students to evaluate their eficiency and to evaluate the usage of the tool. In addition, a research is being conducted to identify studies that use 3D modeling and printing as motivational mechanisms.